Determinan Ketimpangan Distribusi Pendapatan di Pulau Sumatera - Rahmadi, Selamet; Setia Devi Siregar, Rida; Rosmeli, Rosmeli (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine and analyze the dynamics of the development of income inequality as well as the influence of GRDP, population, inflation, HDI, and IP-ICT on income inequality in provinces on the island of Sumatra in 2018–2022. To answer this objective, a descriptive model was used: panel data regression analysis using a random effect model for the period 2018–2022 and 10 provinces on the island of Sumatra. The research results show that the development of income inequality in each province on the island of Sumatra fluctuates except for the Bangka Belitung Islands, which continues to decline during the research year period. The GRDP variable has a positive and significant effect on income inequality; the population variable has a positive and insignificant effect on income inequality; the inflation variable and the human development index have a negative and insignificant effect on income inequality; and the information and communication technology development index variable has a negative and significant effect on income inequality in Sumatra.